Chemical, physical and organoleptic quality test of seaweed (Eucheuma cottonii) jelly candy with the addition of ginger juice and turmeric juice - Setiawati, Veni Rori; Cendana, Sulista (Journal of Agritechnology and Food Processing, 2023)
The rich potential of seaweed in Indonesian seas has been used to produce processed foods such as jelly candy, which is made from fruit juice and gelling agents. Jelly candy has a clear, transparent appearance and a certain chewy texture and is considered a semi-wet food. The aim of this study was to evaluate the effect of the addition of ginger and turmeric juice on the chemical, physical and organoleptic properties of seaweed jelly candy in order to make it acceptable to consumers. In this study, the results obtained showed that the jelly candy had a moisture content of 12%, a sugar content of 16% and a pH of 5.66. The addition of ginger juice and turmeric resulted in a colour lightness value of L* of 23.8 and ⁰Hue of 49.1. Organoleptically, the jelly candies scored positively in terms of colour, aroma, taste and texture. The colour of the jelly sweets received hedonic scores of 3.08 (liked) and 3.36 (brownish-yellow), aroma scores of 2.8 (liked) and 2.48 (less flavourful), taste scores of 2.84 (liked) and 2.56 (slightly ginger and turmeric flavour) and texture scores of 2.76 (liked) and 2.72 (chewy).